What Function Do Platelets Play in Inflammation and Bacterial and Viral Infections? - Tokarz-Deptuła, Beata; Palma, Joanna; Baraniecki, Łukasz; Stosik, Michał; Kołacz, Roman; Deptuła, Wiesław (Frontiers in Immunology, 2021)
The article presents the function of platelets in inflammation as well as in bacterial and viral infections, which are the result of their reaction with the endovascular environment, including cells of damaged vascular endothelium and cells of the immune system. This role of platelets is conditioned by biologically active substances present in their granules and in their specific structures – extracellular vesicles (EV).